Mandatory Affairs Development Transformation in Five Regional Apparatus Organizations Not Related to Basic Services in Badung Regency, Bali - Tingkes, I Nyoman; Sirna, I Ketut; Widnyani, Ida Ayu Putu Sri (Universitas Warmadewa, 2023)
The purpose of this study is to analyze the performance results of five regional apparatus organizations in six mandatory affairs that are not related to basic services. By designing and using a concurrent embedded method approach with comparative descriptive analysis techniques on the LKPJ-2021 document from five regional apparatus organizations. From the results of the study, it was found that (1) the level of conformity and efficiency between budget absorption and the achievement of performance targets in each regional apparatus organization was not optimal, (2) the licensing and non-licensing performance targets were 6,000 permits and non-permits were realized as many as 5,564 permits. This achievement is constrained by Law No. 11, 2020 concerning Job Creation and PP No. 5, 2021 concerning the Implementation of Risk-Based Licensing, (3) settlement activities for compensation and development compensation by the district government with a performance target of 25 plots of land, but the realization results are nil, and (4) technical services, which leave a budget allocation of at least The largest is the Department of Communication and Information, which is Rp. 16,666,316.020.00 or 35.80%. Based on these findings, it is suggested to policymakers to (1) further improve budgeting estimates related to the achievement of performance targets, (2) further strengthen the management of data and information on integrated electronic-based licensing and non-licensing supported by adequate infrastructure, human resources, OSS-BRS, LAPERON, and TRUST applications, and (3) the solution to land problems is prioritized.